PENGARUH PEMBERIAN FOSFAT ALAM DAN BAHAN ORGANIK TERHADAP SIFAT KIMIA TANAH, PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) PADA TANAH SULFAT MASAM POTENSIAL - Iman Saleh Batubara; Fauzi Fauzi; Kemala Sari Lubis (Jurnal Agroekoteknologi, 2014)
This research aims to find out the influence of application organic matter and rock phosphate toimprove soil chemical characteristic, growth and production of rice plant in acid sulphate soils, it isrelated to acid sulphate soils case, such as low pH, high iron (Fe2+) making less production. It isconducted in Faculty of Agriculturegreenhouses, University of North Sumatra, using a randomizedblock design factorial, with 2 factors; organic matter (B), B0 =(0 g /pot); B1 = (40 g straw /pot); B2= (80 g straw/pot); B3 = (40 g cow’s manure/pot); B4 = (80 g cow’s manure/pot); B5 = (26,7 gstraw + 53,3 g cow’s manure/pot) and rock phosphate (P), P0 = (0 g /pot); P1 = (0,64 g rockphosphate /pot); P2 = (1,28 g rock phosphate /pot). The measured parameters were pH, C-organic,P-avaliable, Fe2+, plant height, maximum seedlings and weight of dried grains. The results showedthat organic matter application significantly affected in increasing pH, P-avaliable,maximumseedlings, plant height, weight of dried grains and decreasing Fe2+at final vegetative phase. Rockphosphate application significantly affected in increasing pH, P-avaliable, weight of dried grainsand decreasing Fe2+at final vegetative phase. Combination of the two factors significantly affectedin increasing pH, P-avaliable, maximum seedlings, plant height, weight of dried grains anddecreasing Fe2+at final vegetative phase.Key words: acid sulphate soils, rice plant, organic matter, rock phosphate